Affirmative Reaction : New Formations of White Masculinity - Carroll, Hamilton, 1969- (Book collections on Project MUSE., 2011)
Argues that white masculine privilege has been maintained in the face of broader cultural and economic changes in the U.S. by representing itself as marginalized or minoritized in the very ways that it has been critiqued.